Repetitive negative thinking in daily life and functional connectivity among default mode, fronto-parietal, and salience networks - Lydon-Staley, David M.; Kühner, Christine; Huffziger, Silke; Kirsch, Peter (Translational Psychiatry, 2019)
Repetitive negative thinking (RNT) is a maladaptive response to sadness and a transdiagnostic risk-factor. A critical challenge hampering attempts to promote more adaptive responses to sadness is that the between-person characteristics associated with the tendency for RNT remain uncharacterized. From the perspective of the impaired disengagement hypothesis, we examine between-person differences in blood-oxygen-level-dependent (BOLD) functional networks underlying cognitive conflict signaling, self-referential thought, and cognitive flexibility, and the association between sadness and RNT in daily life. We pair functional magnetic resonance imaging with ambulatory assessments deployed 10 times per day over 4 consecutive days measuring momentary sadness and RNT from 58 participants (40 female, mean age = 36.69 years; 29 remitted from a lifetime episode of Major Depression) in a multilevel model. We show that RNT increases following sadness for participants with higher than average between-network connectivity of the default mode network and the fronto-parietal network. We also show that RNT increases following increases in sadness for participants with lower than average between-network connectivity of the fronto-parietal network and the salience network. We also find that flexibility of the salience network’s pattern of connections with brain regions is protective against increases in RNT following sadness. Our findings highlight the importance of functional brain networks implicated in cognitive conflict signaling, self-referential thought, and cognitive flexibility for understanding maladaptive responses to sadness in daily life and provide support for the impaired disengagement hypothesis of RNT.
Gesehen am 30.10.2019